Oil-Sponsored Exhibitions and Canada’s Extractive Politics of Cultural Production - Sharp, Camille-Mary (Imaginations, 2022)
Focusing on the Canadian Museum of History’s newest permanent exhibition, The Canadian History Hall (2017), and its sponsorship by the Canadian Association of Petroleum Producers (), this article discusses oil-sponsored museum exhibitions and the extractive politics within which Canadian culture is produced. This article begins with an overview of The Canadian History Hall and the activist response to its sponsorship by Big Oil. It then situates the exhibition within a larger history of oil and museums in Canada, reflecting on the controversial, Shell-sponsored The Spirit Sings (1988) exhibition at the Glenbow Museum. The article argues that, as it reproduces the longstanding relationship between Canadian museums and the oil industry, the Canadian Museum of History’s recent partnership exemplifies the ongoing role of extractive politics in cultural production. While European museums increasingly face pressures to divest from fossil fuels, the entanglement of culture and extractive interests in Canada suggests the need for a unique and critical approach to sponsorship in Canadian cultural institutions.